How top level recruitment really happens - Vardy, Anthony (Henry Stewart Talks, 2016)
In this interview Mr Anthony Vardy, who has held leadership positions in two of the five largest global ‘headhunting’ firms, describes, from his own experience, the process by which businesses recruit at the senior level. From the initial brief given to the recruitment consultant to the final selection.